Mesoscale dynamics and its interaction with coastal upwelling in the northern Gulf of Guinea - Thiam, Abdoul Karim; Alory, Gael; Dadou, Isabelle; Napolitano, Dante; Aguedjou, Habib Micaël A.; Cardot, Camille; Morvan, Guillaume; Morel, Yves; Jouanno, Julien (Frontiers in Marine Science, 2024)
Mesoscale dynamics is essential to understanding the physical and biological processes of the coastal ocean regions due to its ability to modulate water properties. However, on the shelf, interactions between eddies, coastal currents, and topography involve complex processes whose observation, understanding, and accurate simulation still pose a major challenge. The purpose of our work is to quantify the mesoscale eddies in the northern Gulf of Guinea, off West Africa (10°W–10°E, 2°N–7°N), and their dynamical interaction with the near-surface ocean particularly in the coastal upwelling that occurs in summer between 2°W and 2°E. We used a regional NEMO model simulation at 1/36° resolution over the 2007–2017 period with daily outputs. A total of 38 cyclonic and 35 anticyclonic eddy trajectories were detected over the 2007–2017 period in July–August–September (JAS), with a mean radius along their trajectories of 95 km and 125 km, respectively. The mean lifetime for cyclones and anticyclones is approximately 1 month with an associated sea-level amplitude between 1 and 2 cm. We then focused on the JAS upwelling period of the year 2016 and found a 73 km radius cyclonic eddy east of Cape Three Points (Ghana) with a lifetime of 1 month which interacted with the coastal upwelling. Indeed, the quasi-stationary eddy dwelled within the coastal upwelling region from mid-July to mid-August 2016. A Lagrangian study shows that the eddy waters come from the coastal upwelling, then mix with warmer offshore waters, and later are transported eastward by the Guinea Current. Using a heat budget analysis, we show that this eddy–coastal upwelling interaction has an impact on sea surface temperature (SST) with a double effect: i) the eddy expands offshore the cold and salty waters (23°C and 35.6) of the coastal upwelling from 14 to 26 July; and ii) from 27 July until its dissipation, the eddy weakens this upwelling by an easterly inflow of warm offshore waters. This study highlights how the eddy–upwelling interaction can modulate the coastal upwelling in the northern Gulf of Guinea.